Carboxylated Multiwalled Carbon Nanotubes as Dispersive Solid-Phase Extraction Sorbent to Determine Eighteen Polychlorinated Biphenyls in Vegetable Samples by Gas Chromatography-Mass Spectrometry - Tengfei Liu; Daifeng Yang; Jian Mao; Xueming Zhang; Minghui Dong (Journal of Analytical Methods in Chemistry)
A simple, rapid, and reliable method based on dispersive solid-phase extraction (d-SPE) and gas chromatography-mass spectrometry (GC-MS) was developed for quantitating polychlorinated biphenyls (PCBs) in vegetable samples. Parameters affecting both the extraction yields and cleanup efficiency, including the type and volume of extraction solvent, extraction time, type and volume of cleanup sorbent, and cleanup time, were optimized. Matrix effects were evaluated, and matrix-matched calibration was recommended. Under the optimized conditions, carboxylated multiwalled carbon nanotubes (MWCNTs-COOH), which exhibit excellent adsorption capabilities due to large surface area and unique structure, were employed as d-SPE sorbent to remove interfering substances, rather than the analytes, from vegetable samples. Satisfactory linear relationship was observed for all PCBs across a concentration range of 5–500 μg/kg with correlation coefficients no less than 0.9993. Four representative vegetables (cucumber, tomato, lettuce, and cabbage) were selected as matrices for method validation. Each matrix was spiked at concentrations of 5, 10, and 100 μg/kg to evaluate recoveries, which ranged from 84.5% to 116.5% with relative standard deviations (n=6) between 0.6% and 17.6%. The limits of detection and the limits of quantification ranged from 0.3 to 1.4 μg/kg and 0.8 to 4.5 μg/kg, respectively. Twelve real vegetable samples were analyzed using the proposed method. Three of the target PCBs were detected in one lettuce sample with the total concentration of 17.9 μg/kg.